Francophonie, concept postcolonial ? - Kalinowska, Ewa (Romanica Silesiana)
The aim of the present analysis is to discuss the francophony as a postcolonial concept, on the basis of the famous article “Pour une littérature-monde en français” whose authors consider the concept of the francophony as a form of colonial domination and are awaiting the birth of world literature in French. This paper explores these issues on the example of Raharimanana, a young writer from Madagascar. Key words: The francophony, world literature in French, post colonialism, Raharimanana.